IMPACT OF HALAL PRODUCTS ON PURCHASE DECISIONS AND CUSTOMER SATISFACTION - Kurniawan Yunus Ariyono (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
Halal is the main parameter in the product selection process. This provision places limitations on food products to enter the Muslim market. Ensuring that food consumed is halal is the responsibility of every Muslim. To make it easier to find out which food is consumed halal, especially packaged foods, it can be seen from the halal label listed on the food packaging. Labels on food products are very important to note. The purpose of this study is to determine and analyze halal products on purchasing decisions and consumer satisfaction. The population in this study were buyers of AZZA mineral water in Lumajang, as many as 150 buyers. The sampling method used in this study was purposive sampling. Methods of data analysis using Simple Linear Regression. The results of this study indicate that halal products have a significant effect on purchasing decisions and consumer satisfaction of AZZA mineral water in Lumajang.